Human Rights Violation Conundrum: Asouzu’s Ibuanyidanda Ontology As A Remedy - Bisong, Peter; ETTA, PETER TAWOR (Advances in Social Sciences Research Journal, 2015)
On a daily basis one hears of killings, rapes, kidnapping and all other sorts of human right abuses from all quarters of the world. This has continued in spite of the Universal Declaration of Human Rights (UDHR) and the various attempts by different bodies and government to halt this trend. It is the believe of the researchers that if the tenets of Ibuanyidanda philosophy are applied and adhered to, human rights violations would reduce to the barest minimum. Ibuanyidanda is a term coined from Igbo language of Nigeria and literarily translates to ‘no load is insurmountable for the ant”. This means that when the ants work in unison, there are capable of carrying loads that appear heavier and bigger than them. It also means that when humans work in complementarity, they would be capable of doing things that they ordinarily would not have succeeded to do. When this understanding take root in individuals, that is the moment, everybody would understand, that the other person is not an ‘external other’ but a ‘complementary other’ upon whom he ought to depend on to live meaningfully. This work urges the various government and agencies in charge of human right protection, to device ways to drum this message to all individuals. It is when everybody see the other in the eyes of complementarity (an extended part of the self), that he would be less likely to violate the rights of the other.